Accuracy and precision of image-based strain measurement using embedded radiopaque markers. (June 2021) - Blokker, Alexandra M.; Getgood, Alan M.; Nguyen, David; Burkhart, Timothy A.; Holdsworth, David W.
Highlights: Small dimeter beads are accurately tracked when inserted into soft tissue structures. Tracked beads can be used to accurately and precisely calculate tissue strains. A bounding box method is more accurate and precise than a masked based method. Abstract: The purpose of this work was to assess the resolution to which micro-CT and intra-operative CT systems can quantify distances between radiopaque fiducial markers. Twenty-two markers were cast in a silicone phantom, then imaged at ten random rotations and translations within the field of view of a micro-CT and an intraoperative CT. A bounding box method and a mask-based weighted binary method were used to calculate the location of all markers in an image, then the Euclidian distance between neighbouring marker coordinates was calculated. The standard deviation in the inter-marker distance measurements from each of the marker position methods across the ten repeated trials was calculated for each marker identification method to provide a measure of the precision of the strain measurement with each scanner. The imaging systems measured 3D distances between markers to within 0.007 mm and 0.028 mm in the micro-CT and intra-operative CT, respectively, using the bounding box method, and to within 0.011 mm and 0.040 mm in the micro-CT and intra-operative systems, respectively, using the weighted-mask method. The bounding box method was found to be the most precise and is highly promising for applications in high resolution regional soft-tissue strain measurements.